Estudio de mercado para el fortalecimiento de la imagen e identidad corporativa de almacenes JUAN ELJURI Cía Ltda. en la ciudad de Quevedo, año 2011. - Alvarado Barrera, Mayra Carolina (2011)
This research Project is to conduct market research to strengthen the image and corporate identity Almacenes Juan Eljuri in the city of Quevedo. Company dedicated to the marketing of appliances. The main objective is to gather relevant information on the level of acceptance of the company in Quevedo and in turn strengthen the image and corporate identity of the company through a promotional scheme conducted in the city. It aims to guide the decisions that the store manager Juan Eljuri should take in developing their roles, with the delivery of marketing strategies that are possible to carry out in the short term. The project consists of the chapters in which different subjects were studied according to the importance they reported to the project, this was limited to the above market research. Chapter one describes the whole company to know the subject under study, ie general background for the challenge. Chapter two describes all the literature with the respective concepts used in the project. The third chapter describes the methodological aspects, techniques and data collection instruments, data sources, population and sample applied in the development of the field work. Chapter four presents the market survey conducted by statistical processing, charting and analysis and interpretation of data. Also perfomed a situational analysis of Almacenes Juan Eljur iand competence. Chapter five presents the conclusions and recommendations, based on information thrown in the previous chapter. Chapter six describes the proposal of a Promotional Plan for Almacenes Juan Eljuuri made, it contains information concerning plan, objective, design the adversiting campaign, communications mix budget and action plan. In chapter seven the respective conclusions are made based on the proposal. In the chapter eight we find recommendations to all those findings detailed in chapter seven. The ninth chapter describes all the references used in the development of this research project. In chapter ten designs are appended advertisements and promotions applied to the promotional plan.